Unifiability In Extensions Of K4 - Gencer, Çiğdem; De Jongh, Dick (Oxford Univ Press, Great Clarendon St, Oxford Ox2 6Dp, England, 2009)
We extend and generalize the work on unifiability of [8]. We give a semantic characterization for unifiability and non-unifiability in the extensions of K4. We apply this in particular to extensions of KD4, GL and K4.3 to obtain a syntactic characterization and give a concrete decision procedure for unifiability for those logics. For that purpose we use universal models.
Keywords: Unification; unifier; provability logic; closed formula; universal model; logic; birleşme; sağlamasının mantığı; kapalı formülü; mantık; evrensel model